Tundra disturbance studies. II. Plant growth forms of human- disturbed ground in the Canadian Far North - Forbes, B. C. (1992)
In Baffin Island and Devon Island, plant associations comprising the same growth forms, and often the same species, were found in various other disturbance types, such as pedestrian trampling, vehicle tracks, organic and inorganic dump sites, and archaeological and contemporary dwellings. Unlike ruderal plants in more temperate regions, many of these species spread almost solely by vegetative means. As a consequence, narrow strips and small patches (≤1 m across) are readily revegetated, particularly when subsurface rhizomes remain intact within the patch, but larger patches recover more slowly, mostly via peripheral invasion. -from Author